Case Report: Post-operative Angioedema After a Laryngeal Mask Airway Application - Soghomonyan, Suren; Fleming, Qian; Bhandary, Sujatha P. (Frontiers in Medicine, 2021)
Angioedema with macroglossia is a rare complication of anesthesia. We present a clinical case of postoperative development of angioedema presenting with macroglossia in a patient receiving chronic therapy with lisinopril, who developed symptoms in the early postoperative period following surgery in a lateral position, when a laryngeal mask airway was used. Possible mechanisms of angioedema and macroglossia development are discussed along with possible underlying predisposing mechanisms and available therapeutic approaches.